Isolation and preliminary identification of some microorganism strains in microbial products used to clean bird's nest houses - Huynh, Thị Thúy Nga; Nguyen, Thị Ngọc Huyền; Nguyen, Hồ Hữu Phước; Khau, Hoàng Kim Giao (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
Today, the use of microbial products in the livestock industry is very popular, for many purposes such as increasing absorption capacity and preventing diseases in livestock or helping to clean the captive environment. This study isolated, identified and surveyed some biological characteristics of microbial strains used for bird’s nest houses. The results of selecting and isolating 7 strains capable of degrading organic matter, including 5 strains of actinomycetes and 2 strains of bacteria. Among them, 2 strains were found to be mobile, 7 strains produce catalase, 3 strains decompose cellulose and 5 strains decompose protein. Using the Sanger method, the strains were identified as Nocardioides luteus, Streptomyces calvus, Mycolicibacterium mageritense, Streptomyces rochei, Microlunatus soli, Bacillus thuringiensis and Bacillus subtilis. From there, it can be used to combine and create many other products for bird’s nest house.